Relationship of intrinsic motivation towards sport, with variables related to a healthy lifestyle. - Leyton, Marta (2019)
This study‘s objective was to determine which lifestyle variables have a direct relationship with motivation towards the practice of physical activity. There was a sample of 858 subjects, aged between 18 and 77 years (41.62 ± 13.30), from different parts of Spain. The instruments used for data collection were the Behavioural Regulation Exercise Questionnaire, for Intrinsic Motivation measurement; the Intentionality to be Physically Active Measurement Scale, for the intention of future practice measurement; and the Healthy Lifestyles Questionnaire, for tobacco consumption, rest, balanced diet and respect for meal schedule variables measurement. The results determined that the Intention to be Physically Active variable was significant as a predictor of Intrinsic Motivation towards sport whereas the variables Rest Habits, Tobacco Consumption, Balanced Diet and Respect for Meals Schedule were not significant. The importance of promoting strategies for increasing intrinsic motivation is emphasized.